RFID dynamic positioning method - Cheng LI; Song-rong QIAN (Tongxin xuebao)
A novel proximity method-RFID dynamic positioning method was presented,using a moving radio frequency identification (RFID) reader to accurately position the target based on reference tag arrays.The major advantage of the method was that through reading tags without any measurement data,e.g.,the time of arrival (TOA) or the received signal strength indication (RSSI),it improved the accuracy of positioning target based on reference tags and a moving reader.The algorithm was simple but useful.Based on the performance of the prototype system,it demonstrated that the proposed system could accurately position in one of the smallest reference tag cell (within dozens of centimeters) and could be deployed easily with low cost,thus has potential application in RFID warehouse management.